2018
DOI: 10.1111/nph.15058
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and trade‐offs among hydraulic safety, efficiency and drought avoidance traits in Amazonian rainforest canopy tree species

Abstract: Predicting responses of tropical forests to climate change-type drought is challenging because of high species diversity. Detailed characterization of tropical tree hydraulic physiology is necessary to evaluate community drought vulnerability and improve model parameterization. Here, we measured xylem hydraulic conductivity (hydraulic efficiency), xylem vulnerability curves (hydraulic safety), sapwood pressure-volume curves (drought avoidance) and wood density on emergent branches of 14 common species of Easte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
125
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(142 citation statements)
references
References 64 publications
(102 reference statements)
14
125
2
1
Order By: Relevance
“…Stepwise multiple regression model for drought tolerance explained along the basis of wood density, rooting depth, and isohydricity (Overall model statistics: RMSE: 0.34, R 2 = 0.63, Adjusted R 2 = 0.52, Prob < F = 0.0154). Similarly to our strong support of our first hypothesis, numerous previous syntheses and database efforts have revealed coordination among vegetation hydraulic traits e.g., [17,32,37,40]. Notably, Chave, et al [3] demonstrated relationships between wood conductivity and conduit diameter, along with relationships between wood density and both growth rate and mortality.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Stepwise multiple regression model for drought tolerance explained along the basis of wood density, rooting depth, and isohydricity (Overall model statistics: RMSE: 0.34, R 2 = 0.63, Adjusted R 2 = 0.52, Prob < F = 0.0154). Similarly to our strong support of our first hypothesis, numerous previous syntheses and database efforts have revealed coordination among vegetation hydraulic traits e.g., [17,32,37,40]. Notably, Chave, et al [3] demonstrated relationships between wood conductivity and conduit diameter, along with relationships between wood density and both growth rate and mortality.…”
Section: Discussionsupporting
confidence: 87%
“…A more complex mathematical framework revealed coordination between stomatal closure and Ψ 50 to reduce the risk of embolism while maintaining transpiration [67,68]. A number of smaller-scale, biome or growth form specific studies (e.g., [12,40,[69][70][71]) have revealed a number of more specific relationships. For instance, Blackman, et al [71] found that among woody Australian plants, at the leaf level Ψ 50 was significantly related to the ratio of vessel wall thickness to lumen breadth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations